The Effect of Work–Life Balance and Work Environment on Employee Performance with Work Motivation as an Intervening Variable at the Department of Agriculture of North Tapanuli Regency - Novita Sari Dewi Hutasori; Mesra B; Sri Rahayu; Muhammad Isa Indrawan (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aimed to examine the effects of work–life balance and work environment on employee performance, with work motivation as an intervening variable, at the Department of Agriculture of North Tapanuli Regency, North Sumatra, Indonesia. The research employed a quantitative associative design to analyze both direct and indirect relationships among variables. The study population consisted of 244 employees, including civil servants (PNS), government employees with work agreements (PPPK), and non-civil servants. Using the Slovin formula with a 10% error tolerance, a sample of 80 respondents was selected through simple random sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS version 3.3.3. The measurement model demonstrated satisfactory validity and reliability, with all indicators meeting the criteria for convergent and discriminant validity, Average Variance Extracted (AVE) values exceeding 0.50, and Composite Reliability values above 0.70. Structural model evaluation revealed that work–life balance has a strong positive and significant effect on employee performance (β = 0.958; t = 39.057; p < 0.001), indicating that employees who are able to balance work responsibilities and personal life tend to perform better. In contrast, the work environment does not have a significant direct effect on employee performance (β = −0.072; t = 0.639; p > 0.05). Furthermore, both work–life balance (β = 0.163; t = 7.296; p < 0.001) and work environment (β = 0.897; t = 45.113; p < 0.001) have positive and significant effects on work motivation. . However, work motivation does not significantly affect employee performance (β = 0.119; t = 0.946; p > 0.05) and does not mediate the relationship between work–life balance or work environment and employee performance. These findings suggest that employee performance improvement is driven primarily by direct work–life balance policies rather than through motivational mechanisms. Managerial implications highlight the importance of implementing effective work–life balance strategies supported by objective performance management systems in public sector organizations.